Grapevine aquaporins: gating of a tonoplast intrinsic protein (TIP2; 1) by cytosolic pH - Leitão, Luís (2019)
Grapevine (Vitis vinifera L.) is one of the oldest and most important perennial crops being considered as a fruit ligneous tree model system in which the water status appears crucial for high fruit and wine quality, controlling productivity and alcohol level. V. vinifera genome contains 28 genes coding for aquaporins, which acting in a concerted and regulated manner appear relevant for plant withstanding extremely unfavorable drought conditions essential for the quality of berries and wine. Several Vv aquaporins have been reported to be expressed in roots, shoots, berries and leaves with clear cultivar differences in their expression level, making their in vivo biochemical characterization a difficult task. In this work V. vinifera cv. Touriga nacional VvTnPIP1;1, VvTnPIP2;2 and VvTnTIP2;1 were expressed in yeast and water transport activity was characterized in intact cells of the transformants. The three aquaporins were localized in the yeast plasma membrane but only VvTnTIP2;1 expression enhanced the water permeability with a concomitant decrease of the activation energy of water transport. Acidification of yeast cytosol resulted in loss of VvTnTIP2;1 activity. Sequence analysis revealed the presence of a His131 residue, unusual in TIPs. By site directed mutagenesis, replacement of this residue by aspartic acid or alanine resulted in loss of pHin dependence while replacement by lysine resulted in total loss of activity. In addition to characterization of VvTn aquaporins, these results shed light on the gating of a specific tonoplast aquaporin by cytosolic pH